2017
DOI: 10.1097/pts.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies Between Two Cross-Cultural Adaptations of the Hospital Survey on Patient Safety Culture Into French

Abstract: Two cross-cultural adaptations of the 12-dimension Hospital Survey on Patient Safety Culture (HSOPSC) into French coexist: the Occelli and Vlayen versions. The objective of this study was to assess the psychometric properties of the Occelli version in comparison with those reported for the Vlayen and the original US versions of this instrument.Methods: Using the original data from a cross-sectional study of 5,064 employees at a single university hospital in France, we examined the acceptability, internal consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Cronbach's alpha was higher than 0.70 across habit subscales (median 0.83; range, 0.72-0.88) and compared favorably with those reported in the original US development (median, 0.66; range, 0.51-0.81) and German cross-cultural adaptation (median, 0.39; range, 0.31-0.46) ( Table 6). This finding contrasts with previous studies that usually report worse performance for crosscultural adaptations in comparison with original standardized instruments [30]. Krupat et al were not concerned by the moderate internal consistency of the original version of the 4-HCS and speculated that successful training in communication would result in more effective communication and therefore greater internal consistency [8].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Cronbach's alpha was higher than 0.70 across habit subscales (median 0.83; range, 0.72-0.88) and compared favorably with those reported in the original US development (median, 0.66; range, 0.51-0.81) and German cross-cultural adaptation (median, 0.39; range, 0.31-0.46) ( Table 6). This finding contrasts with previous studies that usually report worse performance for crosscultural adaptations in comparison with original standardized instruments [30]. Krupat et al were not concerned by the moderate internal consistency of the original version of the 4-HCS and speculated that successful training in communication would result in more effective communication and therefore greater internal consistency [8].…”
Section: Discussioncontrasting
confidence: 60%
“…Second, exploratory factor analysis was performed in order to examine possible alternative structures to the original US version of the 4-HCS. An orthogonal rotation method (Varimax) of factors with eigenvalues higher than 1.00 was used, assuming that they were independent [30]. Primary loadings on intended dimensions higher than 0.40 with cross-loadings lower than 0.30 were considered satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a psychometric tool, HSOPS adaptation versions [ 93 ] are subject to inconsistences due to language and cultural particularities. A previous validation of the tool was not an eligibility criterion in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Construct validity of the AHRQ HSOPSC has been assessed using either exploratory or confirmatory factor analysis. Where exploratory factor analysis was used, the optimal factor structure ranged from 8 to 14 factors (Al Salem et al, 2019;Boussat et al, 2017;Gambashidze et al, 2017;Najjar et al, 2013;Pfeiffer & Manser, 2010;Sorra & Dyer, 2010;Tereanu et al, 2018;Waterson et al, 2019), and the same held true for the confirmatory factor analysis (Eiras et al, 2014;Gambashidze et al, 2017;Nordin et al, 2013;Pfeiffer & Manser, 2010;Sorra & Dyer, 2010;Waterson et al, 2019). Sorra and Dyer (2010) did multilevel psychometric properties examination of the AHRQ HSOPSC on data available from 331 U.S. hospitals and found that the Cronbach's α (a measure of internal consistency reliability) of the individual composites was greater than 0.7 except for the staffing composite which had a Cronbach's α value of 0.62 (Sorra & Dyer, 2010).…”
Section: Introductionmentioning
confidence: 99%